(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aims to study the impact of governance on promoting sustainable development, with a practical application to the National Housing Company. The research addressed the concept of governance, its importance, principles, and objectives, as well as its relationship to the dimensions of sustainable development (economic, social, and environmental) and the requirements for achieving it. It also addressed the challenges facing the implementation of governance and the factors influencing its success. The researcher used a descriptive-analytical approach to collect theoretical information, in addition to an applied approach by studying the reality of governance and sustainable development practices at the National Housing Company through a questionnaire and data analysis. The results highlighted that the National Housing Company applies good governance practices such as transparency, accountability, and participation, and that this has positively reflected on achieving its sustainable development goals, particularly in improving institutional efficiency, promoting social responsibility, and protecting the environment. The research recommended the need to strengthen the company’s institutional governance framework and develop more integrated strategies to achieve sustainable development, with a focus on leadership training, developing disclosure mechanisms, and enhancing stakeholder participation to ensure continuous improvement in this area.